PENERAPAN KARAKTER DISIPLIN SISWA MELALUI PROGRAM EKSTRAKULIKULER PENCAK SILAT PERISAI DIRI SDN 31 CAKRANEGARA - Ramdan, Syukron Zul; Nurlaela, Nurlaela; Dewi, Nurlita (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to describe the implementation of students' discipline through the Perisai Diri pencak silat extracurricular program at SDN 31 Cakranegara. A descriptive qualitative method was used, involving observation, interviews, and documentation. The results show that pencak silat effectively fosters student discipline through structured training, adherence to rules, and instilling responsibility and respect. In addition to being a cultural heritage, pencak silat serves as a character education tool that strengthens students’ positive behavior in both school and community environments.